International criticality benchmark comparison exercise in support of nuclear data validation - Leclaire Nicolas; Duhamel Isabelle; Leal Luiz; Dumont Véronique; Heinrichs Dave; Kim Soon S.; Alwin Jennifer L.; Macquigg M. Robbie; Rising Mike E.; Spencer Kristina Y.; Marshall William J.; Saylor Ellen M. (EPJ Web of Conferences, 2023)
The objective of this paper is to present the main results of the keff inter-comparison exercise performed in 2019-2022 by LANL, LLNL, ORNL and IRSN on a set of common benchmarks. The paper includes a description of the methodology to make the inter-comparison, presents the set of selected cases along with the main tendencies that could be at-tributed to nuclear data. In addition, it identifies some issues on the processing and interpretation of nuclear data done by the various codes of the intercomparison.